2019
DOI: 10.1080/16549716.2019.1599560
|View full text |Cite
|
Sign up to set email alerts
|

Knowing antimicrobial resistance in practice: a multi-country qualitative study with human and animal healthcare professionals

Abstract: Background: Antimicrobial resistance (AMR) is a growing global problem. Raising awareness is central to global and national action plans to address AMR in human and livestock sectors. Evidence on the best ways to reduce antibiotic use, and the impact of awareness raising activities is mixed. This paucity of evidence is acute in Low-Middle-Income Country (LMIC) settings, where healthcare professionals who prescribe and dispense antimicrobial medicines are often assumed to have limited awareness of AMR and limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 33 publications
10
90
0
4
Order By: Relevance
“…As an example, our animation was used alongside other digital materials during AMR awareness week (18-24 November 2019), which led to an additional 1214 new viewers in those 6 days alone. This study supports others that have shown an urgent need for more research into the most appropriate content of AMR awareness campaigns, to ensure that they achieve their intention to effect behavioural changes [18,19]. Future studies should assess to what extent these digital materials impact on behaviours associated with usage.…”
Section: Discussionsupporting
confidence: 82%
“…As an example, our animation was used alongside other digital materials during AMR awareness week (18-24 November 2019), which led to an additional 1214 new viewers in those 6 days alone. This study supports others that have shown an urgent need for more research into the most appropriate content of AMR awareness campaigns, to ensure that they achieve their intention to effect behavioural changes [18,19]. Future studies should assess to what extent these digital materials impact on behaviours associated with usage.…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, and as our results among farmers suggest, solely providing information on antimicrobial use and AMR to agrovets is unlikely to promote more prudent dispensing practices. Indeed, in a survey of agrovets in Africa and Asia, knowledge of AMR did not translate into prudent use (e.g., reduced dispensing) but was linked to less prudent practices (i.e., use of next-line antibiotics) [54]. In addition, the double role played by agrovets-those who give advice that leads to antimicrobial use and those who stand to benefit financially from the sales of antimicrobials-gives rise to moral hazard that must be considered when designing interventions.…”
Section: Integrating Top-down Support With Bottom-up Behavior Change mentioning
confidence: 99%
“…All healthcare professionals (HCPs), including nurses, technicians, pharmacists and physicians, have a responsibility in their clinical practice in keeping ABs effective [12][13][14][15][16][17][18]. Around 90% of AB consumption in human medicine occurs in outpatient settings; therefore, it is imperative to administer these drugs only in cases where it is appropriate [19][20][21].…”
Section: Of 17mentioning
confidence: 99%